UJI DENSITAS DAN POROSITAS SERTA KARAKTERISASI MENGGUNAKAN XRD DAERAH MATA AIR PANAS SEMURUP SUNGAI MEDANG KABUPATEN KERINCI PROVINSI JAMBI - Larlen Nixolas; Nova Susanti; Samsidar Samsidar; Linda Handayani (Komunikasi Fisika Indonesia, 2018)
Test Density and Porosity of rock have been done to see the relation to temperature influence 100 ᵒC, 200 ᵒC and 300 ᵒC. Rocks that will be tested first heated temperature with furnace tool then weighed with a digital balance. Density and Porosity measurement data were analyzed using Matlab Software with ASTMC373 equation. The result of Matlab in the form of graph shows average temperature change to Semurup rock density of 0.03 g / cm3 and the effect of temperature on Semurup rock porosity at 300 ᵒC is 30.29%. The average temperature change to Medang River rock density is 0.003 g / cm3 and the effect of temperature on Medang River rock porosity at 300 ᵒC is 0,55%. Looking at the rock crystal structure used XRD. Data from Characterization using XRD was analyzed with High Score Plus software. The result of rock characterization using XRD, from semurup showed that component of CaCO3 is 94%, crystal structure not yet fully formed and still in amorphous form, meanwhile rock from medang river show that component of CaCO3 is with 98%, crystalline structure have formed crystal.